Sea bass hatchery operations. - Parazo, MM.; Garcia, LMB.; Ayson, FG.; Fermin, AC.; Aaalmedras, JME.; Reyes, DM.; Avila, EM. (Tigbauan, Iloilo Aquaculture Department, Southeast Asian Fisheries Development Center, 1990)
Aquaculture Extension Manual No. 18; July 1990
Keywords: Aquaculture; Fish; Aquaculture; Sea basses